2020
DOI: 10.1136/bmjopen-2019-032476
|View full text |Cite
|
Sign up to set email alerts
|

Time series analysis of total and direct associations between high temperatures and preterm births in Detroit, Michigan

Abstract: ObjectivesPreterm births (PTBs) represent significant health risks, and several studies have found associations between high outdoor temperatures and PTB. We estimated both the total and natural direct effects (independent of particulate matter, ozone and nitrogen dioxide air pollutants) of the prior 2-day mean apparent temperature (AT) on PTB. We evaluated effect modification by maternal age, race, education, smoking status and prenatal care.Design and settingWe obtained birth records and meteorological data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…When environmental temperature exceeds the maternal core body temperature, it causes cutaneous vasodilation and sweat secretion, and decreases uterine and umbilical cord blood flow [10]. If heat-loss mechanisms are inadequate to dissipate heat effectively, the body becomes dehydrated [11,12]. In such conditions, the endocrine system activates and releases the antidiuretic hormone and oxytocin, further decreasing uterine blood flow to the foetus and triggering labour, often prematurely [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When environmental temperature exceeds the maternal core body temperature, it causes cutaneous vasodilation and sweat secretion, and decreases uterine and umbilical cord blood flow [10]. If heat-loss mechanisms are inadequate to dissipate heat effectively, the body becomes dehydrated [11,12]. In such conditions, the endocrine system activates and releases the antidiuretic hormone and oxytocin, further decreasing uterine blood flow to the foetus and triggering labour, often prematurely [12].…”
Section: Introductionmentioning
confidence: 99%
“…If heat-loss mechanisms are inadequate to dissipate heat effectively, the body becomes dehydrated [11,12]. In such conditions, the endocrine system activates and releases the antidiuretic hormone and oxytocin, further decreasing uterine blood flow to the foetus and triggering labour, often prematurely [12]. Heat exposure can cause acute heat stress and release heat-shock protein [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that exposure to high-temperature changes increases the risk of premature birth. 26 , 38 Heat stress could activate the fetal hypothalamic-pituitary-adrenal axis, prompting the placental release of estriol, prostaglandins which could induce labor onset. 38 …”
Section: Discussionmentioning
confidence: 99%
“… 26 , 38 Heat stress could activate the fetal hypothalamic-pituitary-adrenal axis, prompting the placental release of estriol, prostaglandins which could induce labor onset. 38 …”
Section: Discussionmentioning
confidence: 99%
“…These include exposure to a range of toxic substances including air pollution (Liu et al, 2019), cigarette smoke (Soneji and Beltran-Sanchez, 2019), polyfluoroalkyl substances (Sagiv et al, 2018), polybrominated diphenyl ethers (PBDEs;Peltier et al, 2015), phthalate esters (Ferguson et al, 2014), lead (Taylor et al, 2015), and arsenic (Ahmad et al, 2001). Additional factors include infection with pathogenic bacteria (Bianchi-Jassir et al, 2017) and exposure to high outdoor air temperatures (Zhong et al, 2018;Gronlund et al, 2020). On a mechanistic basis, these exposures are thought to act by triggering oxidative stress and/or inflammatory pathways that are part of the normal labor process of weakening the membranes (Menon et al, 2011;Romero et al, 2014;Wallace et al, 2016;Ha et al, 2018).…”
Section: Introductionmentioning
confidence: 99%